Answer:
{x = 1, y = 5
Explanation:
Solve the following system:
{3 y - 10 x = 5 | (equation 1)
{x = y - 4 | (equation 2)
Express the system in standard form:
{-(10 x) + 3 y = 5 | (equation 1)
{x - y = -4 | (equation 2)
Add 1/10 × (equation 1) to equation 2:
{-(10 x) + 3 y = 5 | (equation 1)
{0 x - (7 y)/10 = (-7)/2 | (equation 2)
Multiply equation 2 by -10/7:
{-(10 x) + 3 y = 5 | (equation 1)
{0 x+y = 5 | (equation 2)
Subtract 3 × (equation 2) from equation 1:
{-(10 x)+0 y = -10 | (equation 1)
{0 x+y = 5 | (equation 2)
Divide equation 1 by -10:
{x+0 y = 1 | (equation 1)
{0 x+y = 5 | (equation 2)
Collect results:
Answer: {x = 1 , y = 5